Learning Model to Improve Teenagers’ Self-Esteem and Motivation of Having Achievement - Bambang Samsul Arifin (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2017)
This article presents the process of developing an effective learning model to improve teenagers’ self-esteem and motivation of having achievement. The research used mixed method research. In developing the learning model, the researcher carried out pre-study, development and model validation, and a model testing. The research generated a theoretically and empirically proper learning model to improve teenagers’ self-esteem and motivation of having achievement at pesantren (Islamic boarding school). The learning model which was generated is MPPHM (Model Pembelajaran Peningkatan Harga Diri dan Motivasi /The Learning Model to Improve Self-Esteem and Motivation). This model was able to create the interesting, pleasant, and challenging study ambience to be followed by students. The results showed that it generated pedagogic development, provided the efforts to solve a problem in improving teenagers’ self-esteem and motivation of having achievement, and served as the input for plan, implementation, and development of pesantren or other education institutions. This study was expected to benefit the teachers, principals and parents to pay attention to their children psychosocial factor that influence their children behaviors.